2014
DOI: 10.20450/mjcce.2014.131
|View full text |Cite
|
Sign up to set email alerts
|

Metallomics related to gallium compounds: biochemical and xenobiochemical aspects

Abstract: Issues concerning chemical compounds studied in the framework of metallomics are of interest both for the domain of biochemistry dealing with the metabolization of nutrients and for xenobiochemistry -a different domain of biochemistry dealing with the biodegradation of xenobiotics. In this context, in vivo and in vitro data are reviewed here on inorganic and organo-metallic compounds of gallium (Ga), ranging from cellular and molecular biology to biochemistry and pathobiochemistry and on to pharmacology and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Gallium is a metalloid that has been used in different medical applications, such as the treatment of accelerated bone resorption, autoimmune and infective diseases (Gârban et al, 2014). Using the isotope 67 Ga for imaging in rodents, it has been reported that gallium accumulates in tumour tissues.…”
Section: Galliummentioning
confidence: 99%
“…Gallium is a metalloid that has been used in different medical applications, such as the treatment of accelerated bone resorption, autoimmune and infective diseases (Gârban et al, 2014). Using the isotope 67 Ga for imaging in rodents, it has been reported that gallium accumulates in tumour tissues.…”
Section: Galliummentioning
confidence: 99%
“…Finally, special attention must be paid to the presence of trace elements and molecular groups at the surface or inside the mineral. , These trace elements have been the subject of numerous studies in chemistry or medicine to elucidate their role regarding the crystal formation kinetics , or the morphologic features of the mineral . A recent study highlighted that Zn may have an inhibitory effect on calcium oxalate (CaOx) stone formation, whereas Fe and Cu could promote CaOx stone formation. , The carbonate level of biological apatites is also an interesting feature.…”
Section: Introductionmentioning
confidence: 99%
“…The compound chosen was 8-hydroxyquinoline (8-HQ), a wellcharacterized model ligand that is amenable to ESI-MS and forms strong 1:2 metal:ligand complexes with Cu 2+ at pH 8 (log β 2 = 18.3; Perrin, 1979;Ross et al, 1998). The ability of 8-HQ to form uncharged, lipophilic complexes makes it a viable model for biological metal-ion carriers (Gârban et al, 2014) as well as for marine Cu-complexing ligands. We also present Cu(II)-IMAC data for oceanic and coastal surface waters using multiple detection wavelengths, which enable fractionation of marine Cu ligands based on UV absorbance and IMAC retention times.…”
Section: Introductionmentioning
confidence: 99%